Modelo de optimización de ruta de transporte de tractores en la comuna San José El Ejido de la ciudad de Latacunga. - Guerrero Poaquiza, Christian Daniel (2018)
The research project was carried out through the identification, evaluation and monitoring of the deficient factors in the management and distribution of routes; as well as the poor practices of productive operations. The deficit in the organization, control and management of adequate routes for the accessibility of the people who are part of the organization, causes inappropriate actions and conditions with the management of resources for agricultural work that they have. The descriptive method based on facts is taken as reference in the research; the data collection in the environment through the use of interview, checklist, observation, with the result of a situation analysis. In San José el Ejido community, belonging to Juan Montalvo parish of Latacunga city, the aim is to implement an optimization model of tractors transport route with the purpose of benefiting the commune members. At the same time they could maintain an adequate control to improve the arrival times to the place where is planned to work and thereby reduce costs in its performance. In the investigation it could be noticed that the people of this community are affected with the delay of sowing activities since they can´t work their lands at the right times. Thanks to the elaboration of the optimization model of tractors transport route will reduce the work time, as well as, the maintenance costs and with it the beneficiaries will be able to carry out their crops properly.